Traumatic Bereavements: Rebalancing the Relationship to the Deceased and the Death Story Using the Two-Track Model of Bereavement - Rubin, Simon Shimshon; Malkinson, Ruth; Witztum, Eliezer (Frontiers in Psychiatry, 2020)
Bereavements that occur under external traumatic circumstances increase the risk for dysfunction, trauma symptomatology, as well as disordered and prolonged grief. While the majority of individuals who have experienced traumatic bereavements do not meet formal criteria for Posttraumatic Stress Disorder (PTSD), Persistent Complex Bereavement Disorder (PCBD), or Prolonged Grief Disorder (PGD), the degree of distress and dysfunction for these bereaved can be quite significant. The assessment and intervention paradigms in use with traumatic bereavements often prioritize the trauma and bypass the centrality of the interpersonal loss. By using a bifocal approach in conceptualizing bereavement, the Two-Track Model of Bereavement (TTMB) rebalances the approach to the class of traumatic bereavements. Track I examines biopsychosocial functioning and symptoms of trauma and Track II focuses on the nature of the ongoing relationship with the deceased and the death story that may also have elements of traumatic response. The model and its application serve to identify both adaptive and maladaptive responses to loss along both axes to optimally focus interventions where needed. The story of the death, the psychological relationship with the deceased, and the presence of biopsychosocial difficulties each have a part to play in assessment and intervention. A case study of assessment and intervention following traumatic bereavement due to suicide illustrates how attention to each of these factors in the TTMB can facilitate change. Ultimately, the relational bond with the deceased is a major vector in grief and mourning. Assessment and intervention with traumatic bereavements require attention to dysfunction and symptoms of trauma as well as to the death story and the state of the relationship to the deceased.